Interaction between the gut microbiome and diet in metropolitan Sao Paulo dwellers and rural Amazonian riverine - Cestonaro, Talita (2022)
We investigated the relationship between the gut microbiome composition and diet of rural Amazonian riverines (AMZ) (n=49) and compared them to urban São Paulo dwellers (SP) (n=55). Diet was measured using 24-hour dietary recalls and assessed using an adaptation of NOVA food classification and nutritional composition. Nutrient intake was adjusted using the residual method. Food patterns were investigated using cluster analysis and main sources of nutrients by visual evaluation of bar charts and heatmaps all based on NOVA subgroups. We determined the gut microbiome composition using 16S rDNA sequencing and QIIME 2. Alpha diversity was determined by richness, Pielous evenness, Shannon diversity and Faiths Phylogenetic diversity. Beta diversity was determined by unweighted and weighted Unifrac distances. Differential taxa were determined by ANCOM, COREMIC and PERMANOVA coefficients. Relation between diet and gut microbiome was done using Procrustes analysis and Spearmans rank correlation. P-values were adjusted using false discovery rate (FDR) and significance was defined at adjusted p-value < 0.05 (q-value). AMZ consumed more natural and minimally processed foods (median: 86,25 vs 62,18, Mann-Whitney p <0,001) while SP consumed more processed and ultra-processed foods (median: 6,4 vs 0, Mann-Whitney p <0,001 and median: 28,96 vs 9,94, Mann-Whitney p <0,001, respectively). NOVA subgroups which most contributed to energy intake among AMZ were fish, cassava products, fried dough and crackers while among SP were milk, beef and pork, rice, industrialized and non-industrialized bread, and goodies. SP had more diverse diet than the AMZ. The consumption of most nutrients was statistically different between the two populations, except for energy, carbohydrate, alcohol, and magnesium. SP and AMZ riverine present different gut microbiome compositions that were related to their different dietary patterns. AMZ showed higher alpha diversity and the overall microbiome structure differed between groups (Unifrac, PERMANOVA: Unweighted, p=0.001; weighted, p=0.001). AMZ showed higher abundance of taxa characteristic of traditional societies like Prevotela, Treponema, Succinivibrio and Muribaculaceae while SP showed higher abundance of taxa characteristic of industrialized societies like Alistipes, Bacteroides, Barnesiela, Odoribacter, Parasutterella, Ruminococcus and Parabacteroides. Most differential taxa between populations also presented the strongest significant correlation with diet. Traditional societies taxa positively correlated with AMZ diet specially natural and minimally processed foods, fish, cassava flour, fried dough and their related nutrients like protein, polyunsaturated fat, cholesterol, vitamin B12, vitamin B6, vitamin D and selenium. Industrialized societies taxa positively correlated with SP westernized diet specially processed and ultra-processed foods, milk, industrialized bread, goodies, meat, vegetables, industrialized sauce, homemade desserts, cheese, rice, read-to-eat food products and their related nutrients like monounsaturated, saturated and trans fats, zinc, sodium, iron, copper, calcium, phosphorus, thiamine, riboflavin and vitamin C. AMZ presented Prevotella dominance even having a high animal protein and low fiber diet. Even differences in diet play an important role shaping gut microbiome, we believe that the main driver of this pattern is lifestyle because SP and AMZ are very distinguished societies and differ also in environmental contact, sanitation, hygiene, and other sociocultural practices that potentially affect microorganisms dispersion and consequently their gut microbiome composition.